Nyexon Rock Avalanches: A Special Intrusion Restraint Mechanism, Tibet, China - Cui, Jie; Gao, Chunyu; Zhang, Zhilong; Xiang, Guifu; Liu, Xiong; Huang, Ye (Frontiers in Earth Science, 2022)
The Nyexon Rock Avalanches in the southern Qinghai-Tibet Plateau is a huge scale earthquake-induced slope disaster in the Holocene, the accumulation area has distinct sedimentological characteristics, which is of great significance for studying the intrusion and restraint mechanism during long-distance transportation of large rock avalanches or debris avalanche. This long-distance transportation induced a series of landform types, such as ridges, hills, and ravines; they are widely distributed in all areas and extensively developed shear zones, jigsaw cracks, and other structures within the sedimentary structure. With the analysis of DEM data and geological survey, two main types of basement structures and their transition relationships are distinguished; they play an essential role in the restraining bottom during rock avalanches. In the sedimentary structure, the block facies and mixing facies occupy the main body of the deposition from the center to the distal area. Under the basement restriction, mixing facies are formed between the bottom of the sedimentary layer and the basement sedimentary structure; the shear band is mainly developed along with the mixing facies and basement facies, which is accompanied by basement liquefaction and rheology. A sedimentary facies model is established based on the sedimentary structure sequence of the Nyexon Rock Avalanches transportation. After analyzing the failure mechanism of the rock avalanches, it is believed that in the initial stage of failure, the rock avalanches is transformed into a particle flow that is similar to the debris avalanche, which is restrained by the basement structure and lateral bound; then, an accumulated obstacle highland is formed in the central area after deceleration, making the transportation of the main fluid to deflect quickly.